Norms of evidence in the classification of living fossils - Sterner, Beckett (Frontiers in Ecology and Evolution, 2023)
Some species have held fast for millions of years as constants in a changing world. Often called “living fossils,” these species capture scientific and public interest by showing us the vestiges of an earlier world. If living fossils are defined by a holistic pattern of low evolutionary rates or stasis, however, then classifying a species as a living fossil involves the application of sophisticated norms of scientific evidence. Using examples from Crocodilia and the tuatara (Sphenodon punctatus), I show how scientists’ evidential criteria for classifying living fossils are contentious and underspecified in many cases, threatening the concept’s explanatory interest and its adequacy for sustaining a collective problem agenda as proposed by Scott Lidgard and Alan Love. While debates over the definition of the living fossil concept may appear fruitless, I suggest they can be productive insofar as the debate leads to clarified and improved evidential standards for classification. To this end, I formulate a view of the living fossil concept as an investigative kind, and compare two theoretical frameworks as a basis for shared evidential norms: the Zero Force Evolutionary Law framework, introduced by Daniel McShea and Robert Brandon, and the statistical model selection framework first developed by Gene Hunt in the 2000s.